Modulating effects of temperature on CO2-inhibited isoprene emissions in Eucalyptus urophylla - Pang, Weihua; Zhang, Yanli; Zeng, Jianqiang; Tian, Xiao; Wang, Xinming (Frontiers in Environmental Science, 2024)
Terrestrial vegetation emits substantial amounts of highly reactive isoprene, significantly impacting atmospheric chemistry and climate change. Both atmospheric carbon dioxide (CO2) concentration and temperature can influence plant isoprene emissions; however, whether these factors have a synergistic effect remains unclear, particularly for tropical/subtropical plants. In this study, we conducted in-situ controlled experiments on Eucalyptus urophylla, a representative tropical/subtropical species, to investigate the seasonal variation in the response of isoprene emissions to CO2 concentrations (ISOP-CO2 response) and to identify potential controlling factors. The results showed that high CO2 exerts a nearly linear inhibitory effect on isoprene emissions, as indicated by the slope of the ISOP-CO2 response curve. This inhibitory effect exhibited evident seasonal changes, with stronger suppression during cooler seasons and weaker suppression during warmer seasons. This finding contrasts with the default ISOP-CO₂ response in the MEGAN model, which ignored seasonal variation. Further analysis showed a significant correlation between the slope of the ISOP-CO2 response curve and growth temperature from the past 10 days, indicating that these metrics are effective indicators for predicting seasonal changes. Our findings reveal a synergistic mechanism between temperature and CO₂ concentration effects on isoprene emissions. By coupling the effects of growth temperature with the ISOP-CO₂ response, this mechanism can be integrated into models to provide more accurate predictions of future isoprene emissions, reducing prediction biases, especially during cooler seasons.